Prevalence of vitamin A deficiency in children aged 6-9 years in Wukro, northern Ethiopia - Kassaye Tarik; Receveur Olivier; Johns Timothy; Becklake Margaret R. (The World Health Organization, 2001)
OBJECTIVE: To determine the prevalence of vitamin A deficiency in children aged 6-9 years in northern Ethiopia. METHODS:A cross-sectional study was carried out and the data were analysed for 824 (61.5%) of 1339 eligible children for whom there was complete information on biochemical vitamin A status, dietary vitamin A intake, ocular examination for xerophthalmia, and anthropometry. FINDINGS: The prevalence of xerophthalmia was 5.8%; serum retinol levels were below 0.35 mumol/l and between 0.35 and 0.70 mumol/l in 8.4% and 51.1% of the children respectively. The liver vitamin A reserve (modified relative dose response ratio > 0.06) was low in 41.0% of the children. CONCLUSION: The high prevalence of severe vitamin A deficiency in children aged 6-9 years indicates the need to re-evaluate the practice of targeting vitamin A supplementation programmes on children under 6 years of age in areas where vitamin A deficiency is endemic.